Real-world experience on implantation and atrial signal detection of a SC ICD with atrial sensing capability: The MATRIX study. (19th May 2022) - Maglia, G; Bollmann, A; Theuns, DA; Bar-Lev, D; Anguera, I; Ayala Paredes, FA; Arnold, M; Geller, JC; Merkely, B; Dyrda, KM; Perings, C; Ploux, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): BIOTRONIK, Berlin, Germany Introduction: A single-lead implantable cardioverter-defibrillator (ICD) with atrial sensing dipole (the DX ICD system) can potentially give additive information concerning atrial diagnostics in patients requiring only a single-chamber ICD. We therefore report the real-world experience from large DX registry on implantation, atrial signal quality and detection and the long-term stability of the atrial signal. Methods: The prospective, single-arm MATRIX (Management and Detection of Atrial Tachyarrhythmias in Patients Implanted With BIOTRONIK DX Systems, NCT01774357) registry study effectively enrolled 2041 patients at 119 sites in 24 countries. All patients had a DX system implanted for a single-chamber ICD indication for primary or secondary prevention of sudden cardiac death. Patients were followed for 24 months including remote monitoring. Implantation and follow-up data are reported for the whole patient set. For the analyses on atrial sensing amplitude values, remotely transmitted device measurements of patients without history of long-standing persistent or permanent AF at baseline were used. Results: The mean follow-up period was 677±173 days. Implantation took place at 15±22 days before enrollment. Baseline and implantation data are shown in the table. Implantation procedure and lead insertion were rated as "easy" or "very easy" in 91.0% and 96.3% of assessments, respectively. At implantation, the investigators rated the quality of the atrial sensing amplitude as "sufficient" in 97% of the assessed cases. At enrollment (12-month/24-month follow-up), the atrial signal quality and detection were rated as "good" or "excellent" in 92.3% (89.8%/89.9%) and 92.4% (90.1%/91.3%) of assessments, respectively. For 1841 patients (90.2%), remotely transmitted device information was received. The median (mean ± SD, IQR) transmission rate was 92.5% (85.4±18.2%, 81.4-97.3%). 1746 patients (85.5%) matched the inclusion criteria for the quantitative analyses on atrial sensing. 95.6% of available RA sensing amplitude values were ≥1 mV. Based on each patient's overall median value, the median (mean ± SD, IQR) RA sensing amplitude was 4.6 mV (4.4±2.0 mV, 2.8-6.2 mV). The time course of patient median values stratified by month is shown in the figure. Conclusion: The study followed 2041 patients implanted with the DX ICD system for two years. In the vast majority of cases, investigators rated implantation as (very) easy and the atrial signal over 24 months as good/excellent. According to daily, automatic Home Monitoring data, the overall mean P-wave amplitude remained stable throughout the whole follow-up. The MATRIX study demonstrated functionality and clinical utility of the DX concept in an unselected, real-life setting.